Eggplant Pest Management Strategic Plan (PMSP) - Mark A. Mossler; Olaf Norman Nesheim (EDIS)
This circular describes discussions held between Florida eggplant producing stakeholders and pest management professionals in June 2004. Specific actions for research, education, and regulation are presented in the document.